The major seed proteins of Theobroma cacao L. - Jiirgen Voigt, Bole Biehl; Syed Kamaruddin Syed Wazir
Differential extractions of proteins from Theobroma cacao seeds have revealed the presence of an albumin fraction and a globulin fraction with proportions of